Intraperitoneal doxorubicin achieves access to mesenteric lymph nodes, case series of two patients. (2019) - Sugarbaker, Paul H.; Stuart, O. Anthony
Highlights: Hyperthermic intraperitoneal chemotherapy (HIPEC) is being used increasingly for peritoneal metastases. The distribution of intraperitoneal chemotherapy to target tissues remains poorly described. Access of intraperitoneal doxorubicin to mesenteric lymph nodes was available for determination by HPLC. Data suggests direct access of intraperitoneal doxorubicin to mesenteric lymph nodes in high concentration. High concentrations of intraperitoneal chemotherapy to mesenteric lymph nodes suggests expanded treatment options. Abstract: Background: Intraperitoneal chemotherapy has been used extensively to treat cancers that metastasize to the peritoneal surfaces. In the operating room the intraperitoneal chemotherapy is administered with moderate heat. The chemotherapy is used after surgery when there is minimal residual disease. Alternatively, intraperitoneal chemotherapy can be used long-term in an attempt to prevent the progression of disease in patients at high risk for peritoneal metastases to occur during follow-up. Methods: Hyperthermic intraperitoneal chemotherapy (HIPEC) with doxorubicin was used to treat peritoneal metastases in two patients. These two patients required generous sampling of mesenteric lymph nodes because involvement of these lymph nodes was suspected on preoperative radiologic studies by computed tomography (CT). The lymph nodes, peritoneal fluid and plasma along with tumor tissue in one patient were subjected to a determination of doxorubicin chemotherapy concentrations by high pressure liquid chromatography (HPLC). Results: The ratio of doxorubicin present in peritoneal fluid as compared to plasma was 80 in patient 1 and 50 in patient 2. There was an increased doxorubicin concentration within lymph nodes as compared to plasma. The accumulation of doxorubicin in lymph nodal tissue was 40 times that of plasma in patient 1 and 30 times that in patient 2. In patient 2, the concentration of doxorubicin in lymph nodes was very similar to the concentration of chemotherapy within tumor nodules. Conclusion: Doxorubicin chemotherapy was not only present in peritoneal surface tissue but also a surprisingly high level was present in mesenteric lymph nodes in patients treated by HIPEC. This observation may have implications for interpreting clinical future studies performed with HIPEC. To our knowledge, this is the first time this pharmacologic information regarding intraperitoneal chemotherapy access to mesenteric lymph nodes has been reported.